Implementasi Program Rumah Ilmu Arek Suroboyo (RIAS) dalam Pemenuhan Akses Pendidikan Anak dari Keluarga Miskin di Kota Surabaya - Sherya Damanda; Singgih Manggalou (Institut Pemerintahan Dalam Negeri, 2026)
The phenomenon of school dropouts in Indonesia remains a serious issue despite the implementation of the 12-Year Compulsory Education policy. Surabaya is one of the cities with a relatively high number of school dropouts, prompting the Surabaya City Government to develop the Rumah Ilmu Arek Suroboyo (RIAS) Program as a local adaptation of the national Sekolah Rakyat policy. This program integrates formal education services, dormitory-based caregiving, and character development for children from poor and socially vulnerable families. This study aims to analyze the implementation of the RIAS Program in providing educational and caregiving services for children from low-income families in Surabaya. This research employed a qualitative descriptive approach using the policy implementation theory of Cheema and Rondinelli, which emphasizes environmental conditions, inter-organizational relationships, organizational resources, and the characteristics and capabilities of implementing agents. Data were collected through interviews, observations, and documentation involving program managers, mentors, related government agencies, schools, and foster children. Data analysis was conducted using the interactive model of Miles et al. The findings indicate that the implementation of the RIAS Program has generally been effective through a supportive learning environment, cross-sectoral collaboration among institutions, adequate facilities, and adaptive caregiving approaches. However, the program still faces challenges related to limited human resources and unequal learning assistance for foster children. This study contributes to the development of educational and social policy implementation studies by highlighting an integrated dormitory-based education and caregiving model as a form of local policy adaptation in addressing school dropout issues in urban areas.